A comparison between the TORUS and AFIR axial-flux permanent-magnet machine using finite element analysis - Mahmoudi, A.; Ping, H.W.; Abdul Rahim, N. (2011)
This paper presents a comparison between TORUS and AFIR, the two topologies for double-sided axial-flux permanent-magnet machines. Their slotted and non-slotted topologies were investigated and compared in terms of power density and torque quality. The critical field analysis of the topologies was by finite element method. Results show TORUS topology’s high power-density in high current-density and low electrical-loading. AFIR topology has high power in low currentdensity and high electrical-loading. Non-slotted TORUS and AFIR AFPM machines have negligible cogging torque and lower ripple torque than their slotted counterparts.